Regulation of post-translational modification of PD-L1 and advances in tumor immunotherapy - Feng, Chong; Zhang, Lening; Chang, Xin; Qin, Dongliang; Zhang, Tao (Frontiers in Immunology, 2023)
The immune checkpoint molecules programmed cell death receptor 1 (PD-1) and programmed death ligand 1 (PD-L1) are one of the most promising targets for tumor immunotherapy. PD•L1 is overexpressed on the surface of tumor cells and inhibits T cell activation upon binding to PD•1 on the surface of T cells, resulting in tumor immune escape. The therapeutic strategy of targeting PD•1/PD•L1 involves blocking this binding and restoring the tumor-killing effect of immune cells. However, in clinical settings, a relatively low proportion of cancer patients have responded well to PD-1/PD-L1 blockade, and clinical outcomes have reached a bottleneck and no substantial progress has been made. In recent years, PD-L1 post-translation modifications (PTMs) have gradually become a hot topic in the field of PD-L1 research, which will provide new insights to improve the efficacy of current anti-PD-1/PD-L1 therapies. Here, we summarized and discussed multiple PTMs of PD-L1, including glycosylation, ubiquitination, phosphorylation, acetylation and palmitoylation, with a major emphasis on mechanism-based therapeutic strategies (including relevant enzymes and targets that are already in clinical use and that may become drugs in the future). We also summarized the latest research progress of PTMs of PD-L1/PD-1 in regulating immunotherapy. The review provided novel strategies and directions for tumor immunotherapy research based on the PTMs of PD-L1/PD-1.